Association of CD4-positive cell infiltration with response to vedolizumab in patients with ulcerative colitis - Haruka Miyazaki; Namiko Hoshi; Tsukasa Ishida; Chiharu Nishioka; Sachiko Ouchi; Daisuke Shirasaka; Tomoo Yoshie; Yoshinori Munetomo; Yoshio Sakamoto; Tatsuya Osuga; Saori Matsui; Toshiki Hyodo; et al. (Scientific Reports, 2023)
Abstract Not all patients with ulcerative colitis (UC) respond initially to treatment with biologic agents, and predicting their efficacy prior to treatment is difficult. Vedolizumab, a humanized monoclonal antibody against alpha 4 beta 7 (α4β7) integrin, suppresses immune cell migration by blocking the interaction between α4β7 integrin and mucosal addressin cell adhesion molecule 1. Reports about histological features that predict vedolizumab efficacy are scarce. So, we examined the association between histological features and vedolizumab efficacy. This was a multicenter, retrospective study of patients with UC treated with vedolizumab. Biopsy specimens taken from the colonic mucosa prior to vedolizumab induction were used, and the areas positively stained for CD4, CD68, and CD45 were calculated. Clinical and histological features were compared between those with and without remission at week 22, and the factors associated with clinical outcomes were identified. We enrolled 42 patients. Patients with a high CD4+ infiltration showed a better response to vedolizumab [odds ratio (OR) = 1.44, P = 0.014]. The concomitant use of corticosteroids and high Mayo scores had a negative association with the vedolizumab response (OR = 0.11, P = 0.008 and OR = 0.50, P = 0.009, respectively). Histological evaluation for CD4+ cell infiltration may be helpful in selecting patients who can benefit from vedolizumab.